Psychological symptoms are associated with screen and exercise time: a cross-sectional study of Chinese adolescents - Feng Zhang; Xiaojian Yin; Cunjian Bi; Liu Ji; Huipan Wu; Yuqiang Li; Yi Sun; Sien Ren; Guodong Wang; Xiaofang Yang; Ming Li; Yuan Liu; et al. (BMC, 2020)
Abstract Background Mental disorders among adolescents have become a worldwide public health problem. This study aimed to estimate the best combination of exercise time and screen time to promote the mental health of Chinese adolescents. Methods Participants included 7200 Chinese adolescents aged 13-18 years from six regions of China. Screen and exercise time data were collected via a self-rated questionnaire. Psychological symptoms (e.g., often feeling depressed, school-weary) were evaluated with the "Multidimensional Sub-health Questionnaire of Adolescents". Chi-squared tests and logistic regression analysis were conducted to investigate the differences in and correlations among screen time, exercise time, and psychological symptoms. Results The overall detection rate of psychological symptoms among Chinese adolescents was 21.4% (22.1% for boys and 20.6% for girls). Psychological symptom detection rates were lowest among adolescents with 1-2 h/d of screen time (19.5%) and those with 30-60 min/d of exercise time (17.3%). Screen time > 2 h/d (OR = 1.38, P < 0.001) and exercise time < 30 min/d (OR = 1.62, P < 0.001) were positively correlated with psychological symptoms. Conclusion Screen and exercise time are associated with psychological symptoms in Chinese adolescents. A combination of 1-2 h/d of screen time and 30-60 min/d of exercise time is provided as a reference for better mental health.